Performance e identidade: as práticas musicais do bloco carnavalesco Unidos da Cachorra da cidade de Fortaleza – CE - Monteiro Junior, Francisco Sidney da Silva (2022)
This thesis demonstrates the main constitutive characteristics of the performance of the Grêmio Recreativo Bloco Carnavalesco Unidos da Cachorra in contemporary times, through the ethnography of its practices within its own context of action. Presenting a high revealing potential of personal and collective identities in performance, an attempt was made to detail the different ways in which these are reflected in the experience of socio-musical practices in the group's daily life. From an intense field research with participant observation, it was possible to experience the forms of interactions present in the group's performance: as audience, as rhythmist apprentice and as drummer. Thus, associating the data obtained in the field to the theoretical corpus constructed throughout the research – performance studies and identity - it is argued that the music in the performance of Unidos da Cachorra acts as an articulating element in the formation of a collective identity, understood as a process built through everyday experiences such as rehearsals, instrumental workshops, and parade during the pre-carnival.